The concept of 'actor' in the study of professions: identifying a Western bias - Quddus, S. M. Abdul (Dhaka University Press, 2010)
This paper is based on reviews of literatures on sociology of profession. The paper argues that the concept ‘actors’ has only narrowly mapped the Western literatures related to professionalization of occupations. Such a narrow conception of ‘actor’ in many ways only reflects a convergence of the Western concerns and context and never gives a holistic picture about professionalization of occupations in the context of developing societies. Our point of departure is that such a narrow map and to some extent loose conceptualization about the issue make the concept problematic especially when use in the developing societies like Asia or Africa context. The paper, therefore, draws the conclusion that the understanding and the interpretation of the concept ‘actors’ need to be explained in relation to the wider international socio-economic and political context of a particular society.